Multisystemic Complications in a Patient with Diabetes Mellitus: A Case of Spinal Cord Compression with Chronic Kidney Disease and Diabetic Neuropathy - Putra, I Putu Eka Dharma (Greenation Publisher & Yayasan Global Research National, 2025)
Diabetes mellitus is a major cause of multisystemic complications, particularly in patients with poor glycemic control since a young age. Chronic hyperglycemia induces vascular, neurological, and renal damage, predisposing patients to severe functional impairments and infections. Case Report: We present a 21-year-old male with long-standing uncontrolled diabetes mellitus who developed compressive myelopathy, diabetic kidney disease (DKD), diabetic neuropathy, and neurogenic bladder. The patient exhibited progressive lower limb weakness, urinary and fecal incontinence, chronic back pain, severe hyperglycemia, electrolyte imbalances, and a significant decline in renal function. Discussion: This case illustrates the complex interplay between diabetic microvascular and neurological complications. Chronic hyperglycemia led to glomerular hyperfiltration and progressive renal injury, while peripheral and autonomic neuropathy resulted in debilitating sensory-motor symptoms and recurrent urinary tract infections. The overlapping pathologies highlight the necessity for early screening, aggressive metabolic control, and a multidisciplinary approach to management. Conclusion: Early diagnosis and prompt multidisciplinary intervention are critical to prevent irreversible multisystem damage in patients with longstanding diabetes. Comprehensive management strategies focusing on infection control, renal protection, neuropathic pain relief, and glycemic stabilization are essential to optimize patient outcomes.